Faktor yang Memengaruhi Willingness To Pay More Generasi Z Terhadap Produk Personal Care Eco- Friendly di Area BSD-GS - Chandra, Cherill; Putra Atmodjo, Nicholas Hokio; Rahman, Fathony; Murniadi, Khrisnamurti (Universitas Prasetiya Mulya, 2024)
Environmental issues are currently being widely discussed, especially among young people, particularly Generation Z. This has naturally led to new trends and opportunities, namely the adoption of green consumption patterns and the shift towards environmentally friendly products. However, environmentally friendly personal care products tend to be more expensive than conventional products. A fundamental question arises: what factors influence Generation Z's willingness to pay more for environmentally friendly personal care products? By combining studies conducted by Anil Kumar and Rituparna Basu and by Francesca De Canio on willingness to pay more and its relevance to the influence of eco-labels, the Theory of Planned Behavior or TPB will be used as the main theoretical basis in this research. The research method used is quantitative with a sampling technique using convenience sampling involving 278 Generation Z respondents residing in BSD-GS. Data collection was carried out through the distribution of online structured questionnaires. The results of this study prove that the presence of eco-labels and environmentally friendly product packaging itself has a significant influence on the willingness to pay more of Generation Z consumers in the BSD-GS area. In the context of this research, the Theory of Planned Behavior and awareness of personal health and environmental issues also do not play a role in influencing Generation Z's willingness to pay more for eco-friendly products, especially in the personal care category.